The The Influence of Microfinance Programmes on Women Owned SME Development in Mashonaland West Province of Zimbabwe - Comfort Zvirikuzhe (Journal of Social Science, 2022)
Women have benefited greatly from financial support from a variety of sources, including MFIs, in their active participation and involvement in the expansion of the economy and the creation of employment possibilities in the small and medium firm sector. The prosperity of society is largely attributed to Women Small and Medium Enterprises (SMEs) development, which is also linked to economic growth and development, bettering living conditions, generating new employment opportunities, and technical advancement. This study sought to establish the Influence of Microfinance products on women-owned SMEs development in Mashonaland west province of Zimbabwe. . A pragmatist paradigm research philosophy was adopted. A mixed research approach was used. A cross sectional survey research design a self-constructed structured questionnaire and an interview guide was used to collect data. The study targeted women SMEs who have been receiving Microfinance services in Mashonaland West Province of Zimbabwe. Three hundred and seventy seven women SMEs were exposed to the questionnaire and 30 were exposed to interviews. Descriptive statistics such as mean and standard deviation were used for data analysis. To test the research hypothesis the researcher used structural equation modelling in AMOS and data collected was presented in tables and figures. Cronbach’s alpha (α) was used to determine reliability after data collection and the researcher tested for discriminant validity by comparing average variances extracted (AVE) against squared inter construct correlations. The study found out that the women SMEs are aware of the Microfinance products and services and are using some of the products. It was also found that there is a positive relationship between Microfinance products and women-owned SMEs development. However MFIs are not offering non-financial products to women SMEs and also Microfinance institutions are putting more societal pressure on poor women by extorting money from them with excessive interest rates. . Also lack of collateral was another barrier which hinders women from accessing MFIs products. These findings add something new to the body of existing knowledge. The government is argued to intervene so that MFIs would charge reasonable rates and also MFIs to provide the appropriate products that helps women-owned SMEs to develop. Finally, it is suggested that similar research be conducted with MFIs management and employers as responders. This could result in fresh contributions to the study.